Chapter Marine litter surveys on Boccasette beach (Rovigo, Italy) - Buoninsegni, Joana (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
This study aims to evaluate the presence of marine litter in relation to the main human activities and during some different meteorological conditions. Five surveys were performed along Boccasette spit to collect the stranded items, in order to assess the density of debris and the beach cleanliness. The main litter macro-category is represented by artificial polymer materials (96%), while the others macro-categories represent the 4% of collected items. The main sources of the marine litter have been attributed to improper waste disposal and fishing/aquaculture activities.